2016
DOI: 10.1177/2167696816666974
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Parental Emotional Support and Psychological Control in Early Adulthood

Abstract: Early adulthood is a critical period during which real-world adjustment sets the stage for lifelong well-being. However, little is known about how the emotional quality of parental relationships may help or hinder adjustment. This longitudinal study investigated (a) changes in mother and father emotional support and psychological control during early adulthood, (b) whether such changes predicted young adults' educational and occupational adjustment, and (c) whether these associations occurred indirectly throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 48 publications
3
21
2
Order By: Relevance
“…Work characteristics were assessed using items developed for the V-HYS. Youth listed all jobs held since the last interview on a 24 month-by-month timeline (Desjardins and Leadbeater 2017; Leadbeater and Ames 2017). Youth provided additional information for each job held which were used to create the following work characteristic variables: (1) current employed status (i.e., not employed and employed part-time (0; < 30 h per week), employed full-time (1; ≥ 30 h per week)).…”
Section: Methodsmentioning
confidence: 99%
“…Work characteristics were assessed using items developed for the V-HYS. Youth listed all jobs held since the last interview on a 24 month-by-month timeline (Desjardins and Leadbeater 2017; Leadbeater and Ames 2017). Youth provided additional information for each job held which were used to create the following work characteristic variables: (1) current employed status (i.e., not employed and employed part-time (0; < 30 h per week), employed full-time (1; ≥ 30 h per week)).…”
Section: Methodsmentioning
confidence: 99%
“…To the best of our knowledge, this is the second study (with the exception of Desjardins & Leadbeater, 2016) to document the frequency of psychological control in an agerepresentative sample of emerging adults. On average, emerging adults reported similar low levels of maternal and paternal psychological controls (i.e., in between "not like" and "somewhat like" him/her) that accords with previous research using college student samples (i.e., Desjardins & Leadbeater, 2016;Luyckx et al, 2007). Assimilating our findings with this literature, parental psychological control seems relatively stable at low to moderate levels regardless of parent gender and emerging adult age and college status.…”
Section: Descriptive Statistics Implicationsmentioning
confidence: 97%
“…A thorough review of the emerging adulthood literature identified only 15 papers that investigated psychological control to some capacity (e.g., Desjardins & Leadbeater, 2016;Inguglia et al, 2016;Urry et al, 2011). The lack of literature on psychological control in emerging adulthood is problematic considering psychological control is used more prominently by both mothers and fathers with emerging adult children than behavioral control or helicopter parenting (Padilla-Walker & Nelson, 2012) and because it has consistently been linked to emerging adult maladjustment.…”
Section: Psychological Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…Nearly 20% of the 18-to 25-year-olds endorsed using marijuana in the past month and around 38% of the 18-to 25-year-olds endorsed binge drinking in a 2014 survey (Center for Behavioral Health Statistics and Quality, 2015). Not only does substance use peak at this time, but adjustment experiences during early adulthood have critical implications for an individual's well-being for years to come (Desjardins & Leadbeater, 2017).…”
Section: Introductionmentioning
confidence: 99%